Differential expression patterns of purinergic ectoenzymes and the antioxidative role of IL-6 in hospitalized COVID-19 patient recovery - Mazzocco, Yanina Luciana; Bergero, Gastón; Del Rosso, Sebastian; Eberhardt, Natalia; Sola, Claudia; Saka, Héctor Alex; Villada, Sofía María; Bocco, José Luis; Aoki, Maria Pilar (Frontiers in Immunology, 2023)
Introduction We have acquired significant knowledge regarding the pathogenesis of severe acute respiratory syndrome caused by coronavirus 2 (SARS-CoV-2). However, the underlying mechanisms responsible for disease recovery still need to be fully understood. Methods To gain insights into critical immune markers involved in COVID-19 etiopathogenesis, we studied the evolution of the immune profile of peripheral blood samples from patients who had recovered from COVID-19 and compared them to subjects with severe acute respiratory illness but negative for SARS-CoV-2 detection (controls). In addition, linear and clustered correlations between different parameters were determined. Results The data obtained revealed a significant reduction in the frequency of inflammatory monocytes (CD14+CD16+) at hospital discharge vs. admission. Remarkably, nitric oxide (NO) production by the monocyte compartment was significantly reduced at discharge. Furthermore, interleukin (IL)-6 plasma levels were negatively correlated with the frequency of NO+CD14+CD16+ monocytes at hospital admission. However, at the time of hospital release, circulating IL-6 directly correlated with the NO production rate by monocytes. In line with these observations, we found that concomitant with NO diminution, the level of nitrotyrosine (NT) on CD8 T-cells significantly diminished at the time of hospital release. Considering that purinergic signaling constitutes another regulatory system, we analyzed the kinetics of CD39 and CD73 ectoenzyme expression in CD8 T-cells. We found that the frequency of CD39+CD8+ T-cells significantly diminished while the percentage of CD73+ cells increased at hospital discharge. In vitro, IL-6 stimulation of PBMCs from COVID-19 patients diminished the NT levels on CD8 T-cells. A clear differential expression pattern of CD39 and CD73 was observed in the NT+ vs. NT-CD8+ T-cell populations. Discussion The results suggest that early after infection, IL-6 controls the production of NO, which regulates the levels of NT on CD8 T-cells modifying their effector functions. Intriguingly, in this cytotoxic cell population, the expression of purinergic ectoenzymes is tightly associated with the presence of nitrated surface molecules. Overall, the data obtained contribute to a better understanding of pathogenic mechanisms associated with COVID-19 outcomes.